Analisis Kinerja Jalan Soekarno-Hatta Pekanbaru (Studi Kasus: Depan Mall Transmart) - Antos Gazali; Elianora Elianora; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The decrease of road verformance is due to various factors such as the activities on the side of the road. These activities include side barriers, such as in and out vehicles, stopping vehicles, roadside parking, and pedestrians. Soekarno-Hatta Road in front of Transmart mall is currently experiencing a performance decreased during peak hours due to the increasing volume of traffic flow caused by the activity of the vehicles that going in and out fromTransmart mall. The purpose of this study is to analyze the traffic performance on the Soekarno-Hatta road in front of the Transmart Mall and find solutions to solve the problemthere. Road performance calculation method in this study was referenced to Indonesian Road Capacity Manual (MKJI 1997). The traffic data wer calculated over four days. Based on theanalysis of existing conditions at the highest peak hours occurred on Saturday at 16:15 to 17:15 pm with the result Q = 2553 pcu/hour, C = 3234 pcu/hour and DS = 0,79. Therequirement of DS < 0,75 (MKJI 1997), while the existing DS is 0,79, exceeds the MKJI requirement, so it needs a certain traffic arrangement to improve the performance of the road.One of the alternative improvement is widening the road by 5 m, from the initial width of 7 m to 12 m, This widening decreases DS value to 0,5 which is fulfill DS requirement (DS <0,75).Keywords: Soekarno-Hatta Road, Road Performance, Side Barriers, MKJI 1997